Estimation of Erosion Potentials through Utilization of Remote Sensing Data and The Universal Soil Loss Equation Model - Arif Faisol; Mashudi Mashudi (The University of Lampung, 2023)
Remote sensing data and USLE models have been used widely for erosion analysis. In Indonesia, the USLE model is a reference in erosion analysis to assess land suitability for agricultural crop development. Erosion analysis using remote sensing data provides various advantages, including good accuracy, lower costs, and can analyze erosion rates quickly compared to direct measurement methods. The aim of this study was to analyze the potential erosion in the Arui watershed - Manokwari Regency – West Papua Province using remote sensing data and USLE models. The research was conducted from April to July 2022, with three main stages i.e data inventory, data analysis, and erosion rate estimation. The research shows that the potential erosion rate in the Arui watershed is 15 tons/ha/year or 3.480 tons/year, thus exceeding the tolerable soil loss (TSL) erosion rate threshold of 9.6 tons/ha/year. Therefore, a conservation and restoration program is needed to control the erosion rate in the Arui watershed. Keywords: Erosion rate, Remote sensing, Tolerable soil loss, USLE, Watershed